Effectiveness of Payment System Cash on Delivery (COD) To Businessmen - Noviani, Laila; Nugroho, Andriyanto Adhi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The advent of online shopping has revolutionized the way consumers make purchases, offering a diverse range of payment options for goods bought online. This study aims to examine the effectiveness and potential issues arising from the implementation of Cash on Delivery (COD), a widely used payment method. Employing a juridical-empirical approach, the research gathers insights through interviews with individuals and businesses that utilize COD in their online stores. Additionally, it examines relevant laws governing business protection (for both sellers and buyers). The study reveals that business owners perceive COD to be detrimental due to the high incidence of unilateral order cancellations by buyers upon package delivery. In response to these concerns, the research emphasizes the need for regulations that safeguard business interests, as outlined in consumer protection laws.